2019
DOI: 10.1002/admt.201800639
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Manufacturing of Large and Flexible Sheets of MXene/Graphene Heterostructures

Abstract: been reported as potential electrodes for energy storage. These 2D materials demonstrate unique properties, including high electronic conductivity, high capacity, flexibility, strength, and electrochemical stability. However, all of these materials have limitations in energy storage, such as the low electronic conductivity of oxides and the limited redox activity of graphene-based materials, and limiting charge storage capacity. [1a,7] The challenge, therefore, is to fabricate electrodes that will combine all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 70 publications
0
76
0
1
Order By: Relevance
“…However,t his is not surprising as it was previously reported that MXenes can undergo redox reactions and exhibit pseudocapacitive behaviors. Although it was previously reportedt hat rate performance of MXene electrodes can be greatly improved if open architectures are used, such as macroporouss tructures, [16] vertically aligned nanosheets, [23] or compositesw ith spacers between layers, [24] it is not the goal of this work. In 1 m,4m,a nd 8 m aqueous MSA electrolytes, two redoxr eaction couples can be distinguished, whereas only one redox couplew ith broader peaks can be identified in neat MSA.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However,t his is not surprising as it was previously reported that MXenes can undergo redox reactions and exhibit pseudocapacitive behaviors. Although it was previously reportedt hat rate performance of MXene electrodes can be greatly improved if open architectures are used, such as macroporouss tructures, [16] vertically aligned nanosheets, [23] or compositesw ith spacers between layers, [24] it is not the goal of this work. In 1 m,4m,a nd 8 m aqueous MSA electrolytes, two redoxr eaction couples can be distinguished, whereas only one redox couplew ith broader peaks can be identified in neat MSA.…”
Section: Resultsmentioning
confidence: 98%
“…This is attributed to the factt hat horizontally restacked nanosheets impede high ion diffusivity through the electrode. Although it was previously reportedt hat rate performance of MXene electrodes can be greatly improved if open architectures are used, such as macroporouss tructures, [16] vertically aligned nanosheets, [23] or compositesw ith spacers between layers, [24] it is not the goal of this work.…”
Section: Resultsmentioning
confidence: 98%
“…E and F, Schematic and digital images of flexible 2D MXene/graphene films. Reproduced with permission from Reference . Copyright 2019, Wiley‐VCH.…”
Section: Preparation Methods Of Different Graphene‐based Flexible Elementioning
confidence: 99%
“…graphene films could be obtained by chemical vapor deposition (CVD) and transferred to flexible substrates by a roll‐to‐roll transfer method . Very recently, Gogotsi's group fabricated 2D graphene‐based heterostructured papers by spray‐assisted layer‐by‐layer assembly (Figure E). The rGO dispersion and MXene colloidal solution were sprayed alternately onto the polypropylene membrane and the obtained heterostructured film showed excellent flexibility, without structural damage under different bending states (Figure F).…”
Section: Preparation Methods Of Different Graphene‐based Flexible Elementioning
confidence: 99%
“…Furthermore, the rich surface chemistries that are accessible by well-dispersed 2D materials are obstructed if restacking is prevalent. 60 For example, MoS 2 transitions from an indirect to a direct band-gap semiconductor as its thickness is reduced to a monolayer, and LbL techniques have been demonstrated as a method to drastically improve photoluminescence efficiency as a result of controlled separation of flakes (Table 1). 56 LbL also allows for versatile structuring of 2D materials into three-dimensional (3D) architectures and onto particulate surfaces.…”
Section: Advantages Of Lbl For 2d Materials Assemblymentioning
confidence: 99%